2013
DOI: 10.1021/es400129s
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Levels and Speciation from Ingestion Exposures to Biomarkers in Shanxi, China: Implications for Human Health

Abstract: Chronic exposure to arsenic (As) threatens human health. To systematically understand the health risks induced by As ingestion, we explored water and diet contributions to As exposure, and compared As in biomarkers and the arsenicosis in a geogenic As area in China. In this study, high percentages of water (77% of n = 131 total samples), vegetables (92%, n = 120), cereals (32%, n = 25), urine (70%, n = 99), nails (76%, n = 176), and hair (62%, n = 61) contained As higher than the acceptable levels. Dietary As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 33 publications
3
52
0
1
Order By: Relevance
“…Then, the ternary suspension was mixed for 24 hr at pH 7.0 ± 0.1, and filtered through a 0.4 μm membrane. The soluble As concentration in the filtrate was determined with an atomic fluorescence spectrometer (AFS, Ruiguang, China) with a detection limit of 0.6 μg/L (Cui et al, 2013). Triplicate adsorption experiments were performed and averaged values were reported.…”
Section: Batch Adsorption Experimentsmentioning
confidence: 99%
“…Then, the ternary suspension was mixed for 24 hr at pH 7.0 ± 0.1, and filtered through a 0.4 μm membrane. The soluble As concentration in the filtrate was determined with an atomic fluorescence spectrometer (AFS, Ruiguang, China) with a detection limit of 0.6 μg/L (Cui et al, 2013). Triplicate adsorption experiments were performed and averaged values were reported.…”
Section: Batch Adsorption Experimentsmentioning
confidence: 99%
“…Arsenic-induced skin lesions are endemic in many remote mountainous regions in China, especially in the Shanyin district (Guo et al, 2003). Average arsenic concentrations in groundwater there are nearly 17 times higher than the United States Environmental Protection Agency guideline of 10 mg/ L, and typical clinical features of hyperkeratosis of palms and soles are observed (Cui et al, 2013). Previous work has found that individuals in this region had higher arsenic content in hair and nail than the average Chinese, consistent with arsenic induction of dermatological lesions (Cui et al, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…Average arsenic concentrations in groundwater there are nearly 17 times higher than the United States Environmental Protection Agency guideline of 10 mg/ L, and typical clinical features of hyperkeratosis of palms and soles are observed (Cui et al, 2013). Previous work has found that individuals in this region had higher arsenic content in hair and nail than the average Chinese, consistent with arsenic induction of dermatological lesions (Cui et al, 2013). Those people with noncancerous skin lesions are at high risk of developing skin and internal cancers (Mead, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…The As speciation was determined using high-performance liquid chromatography (HPLC) coupled with a hydride generation atomic fluorescence spectrometer (HG-AFS-8130, Jitian, Beijing, China) installed in a local farmer's house (Cui et al, 2013). Briefly, online separation of As species was carried out with a Hamilton PRP-X100 anion exchange column, using 15 mmol/L phosphate buffer at pH 6 as mobile phase at 1.0 mL/min flow rate.…”
Section: Discussionmentioning
confidence: 99%
“…FS (industrial grade, 21% as Fe) and PFS (industrial grade, 22% as Fe) were obtained from Bodi Chemical Co. Ltd. Tianjin, China. Ten groundwater samples (G1-G10 in Table 1) were randomly collected from Shanxi, China, where As contamination in groundwater prevails (Cui et al, 2013;Luo et al, 2012), and were used to evaluate water chemistry influences on As removal. Because the average As concentration in local groundwater was about 300 μg/L as reported in our previous study (Luo et al, 2012), three samples containing comparable or higher As levels including 321 μg/L (G5), 578 μg/L (G8), and 1067 μg/L (G10) were selected for further study.…”
Section: Methodsmentioning
confidence: 99%